The identity of Kalanchoe stearnii (Crassulaceae subfam. Kalanchooideae) - Smith, Gideon F.; Shtein, Ronen (Phytotaxa, 2021)
In the most recent synoptic treatment of Kalanchoe Adanson (1763: 248) (Crassulaceae subfam. Kalanchooideae), the name K. stearnii Raymond-Hamet (1941: 334), as ‘Stearni’, was interpreted as not having been validly published, with Turland et al. (2018: Art 32.1c) cited as the reason (Descoings 2003: 144). However, the name complied with the requirements applicable at the time for valid publication.